A Comparative Study of the Secondary Metabolite from Talinum triangulare (Jacq.) Willd. Methanolic Extract from Malang and Kediri, East Java - Budiarti, Sarah Fadilah; Fatchiyah, Fatchiyah (Biotropika: Journal of Tropical Biology, 2022)
Talinum triangulare is a medicinal plant that has been used broadly by the Indonesia community because of its properties. Several studies have proven the components of secondary metabolites in T. triangulare. However, the content of secondary metabolites in each part of T. triangulare is not clearly understood. Therefore, this study aimed to analyse the types of secondary metabolites of leaf, stems, and roots of T. triangulare. The plant from Malang was chosen as the sample source because it is a highland suitable for the life of T. triangulare. The plant from Kediri was chosen as a lowland location. Samples of leaves, stems, and roots of T. triangulare were extracted by maceration method. Phytochemical analyses include phenolics, flavonoids, alkaloids, tannins, saponins, and terpenoids. The absorbance values were measured at different wavelengths. The leaf and stems of T. triangulare contain flavonoid compounds, tannins, phenolics, alkaloids, saponins, and terpenoids with higher levels of secondary metabolites in the leaf. While the roots have the lowest secondary metabolite was only containing steroids. The differential levels and types of secondary metabolites samples obtained from Kediri tend to be lower than samples obtained from Malang. These results indicate that the leaf metabolite secondary of T. triangulare has high potential health benefits for regulating molecular and cellular metabolism.